The interactive impact of government size and quality of institutions on economic growth- evidence from the states of India - Nupur Nirola; Sohini Sahu (Heliyon, 2019)
This paper investigates the impact of government size on economic growth across 23 states in India between 2005 and 2014 for varying degrees of quality of institutions. Using pooled OLS, panel random effects estimation, as well as system-GMM estimation techniques, we find that in general, akin to findings in the literature, a bigger government is detrimental for state-level economic growth. However, the extent of the negative growth impact depends on the quality of institutions of the states, measured by a newly available index. States that have better quality of institutions register a lower negative impact on economic growth compared to their less progressive counterparts for similar increase in government size. Also, reduction in non-development government expenditure has a better growth impact compared to reduction in development government expenditure, especially for higher levels of institutional quality. Our results, that are robust to various specifications of government size, quality of institutions and estimation techniques, lead us to conclude that state governments should emphasize on quality of institutions to enhance state-level economic growth.